2021
DOI: 10.7554/elife.64694
|View full text |Cite
|
Sign up to set email alerts
|

An expanding manifold in transmodal regions characterizes adolescent reconfiguration of structural connectome organization

Abstract: Adolescence is a critical time for the continued maturation of brain networks. Here, we assessed structural connectome development in a large longitudinal sample ranging from childhood to young adulthood. By projecting high-dimensional connectomes into compact manifold spaces, we identified a marked expansion of structural connectomes with the strongest effects in transmodal regions during adolescence. Findings reflected increased within-module connectivity together with increased segregation, indicating incre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 175 publications
(362 reference statements)
3
65
0
Order By: Relevance
“…Together, these developmental effects served to further distinguish the functional hierarchy that is now well described in adults, and broadly aligns with recent reports using independent methods and datasets (Dong et al, 2020;Nenning et al, 2020). This functional differentiation of cortical hierarchy over development is consistent with evidence that cortical myeloarchitecture further differentiates between unimodal and transmodal regions during adolescence (Paquola et al, 2019), and that transmodal structural networks become increasingly dissimilar from unimodal networks with age (Park et al, 2021). Coupling between hierarchically similar networks may be partially attributable to the propagation of cortical waves along functional hierarchies (Mitra and Raichle, 2016;Matsui et al, 2016;Gu et al, 2021); however, additional research is needed to examine how such waves evolve in development.…”
Section: Functional Network Development Differs By Position In a Unimodal To Transmodal Hierarchysupporting
confidence: 85%
“…Together, these developmental effects served to further distinguish the functional hierarchy that is now well described in adults, and broadly aligns with recent reports using independent methods and datasets (Dong et al, 2020;Nenning et al, 2020). This functional differentiation of cortical hierarchy over development is consistent with evidence that cortical myeloarchitecture further differentiates between unimodal and transmodal regions during adolescence (Paquola et al, 2019), and that transmodal structural networks become increasingly dissimilar from unimodal networks with age (Park et al, 2021). Coupling between hierarchically similar networks may be partially attributable to the propagation of cortical waves along functional hierarchies (Mitra and Raichle, 2016;Matsui et al, 2016;Gu et al, 2021); however, additional research is needed to examine how such waves evolve in development.…”
Section: Functional Network Development Differs By Position In a Unimodal To Transmodal Hierarchysupporting
confidence: 85%
“…Childhood and adolescent brain development involves dynamic and complex structural changes that are shaped by genetic and environmental factors (Shaw et al, 2006(Shaw et al, , 2007Raznahan et al, 2011;Schmitt et al, 2014;Khundrakpam et al, 2017;Park et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Childhood and adolescent brain development involves dynamic and complex structural changes that are shaped by genetic and environmental factors (Shaw et al ., 2006, 2007; Raznahan et al ., 2011; Schmitt et al ., 2014; Khundrakpam et al ., 2017; Park et al ., 2021). Longitudinal neuroimaging studies have consistently reported a global increase in cortical volume, thickness, and surface area that typically peaks in late childhood and is followed by decreases in adolescence (Raznahan et al ., 2011; Wierenga et al ., 2014; Tamnes et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is controlled by two parameters α and t, where α controls the influence of the density of sampling points on the manifold (α = 0, maximal influence; α = 1, no influence) and t controls the scale of eigenvalues of the diffusion operator. We set α = 0.5 and t = 0 to retain the global relations between data points in the embedded space, following prior applications [17,20,28,41,46,98,99]. Cortical regions with more similar inter-regional patterns are more proximal in this new structural manifold.…”
Section: Structural Manifold Identificationmentioning
confidence: 99%
“…Prior MRI literature has assessed regional changes in brain structure [1][2][3][10][11][12][13][14][15][16], showing age-related widespread decreases in cortical thickness [1,13], as well as increases in intracortical myelin [15][16][17]. Complementing these regional changes, diffusion and functional MRI studies showed an ongoing maturation of both the microstructure of inter-connecting white matter tracts as well as large-scale developmental changes in functional network organization, indicative of shifts in brain connectivity towards a more distributed topology [18][19][20]. Utilizing multimodal longitudinal MRI analyses, here, we explored how adolescent structural network development gives rise to potential shifts in functional network architecture.…”
Section: Introductionmentioning
confidence: 99%